Analisis Kesesuaian Penyimpanan Obat di Puskesmas Wonosobo dan Siring Betik Kabupaten Tanggamus - Ageng Hasna Fauziyah; Muhammad Naufal Aliffy Firdaus (Pusat riset dan Inovasi Nasional, 2024)
The storage of medicines and medical consumables is a management process to ensure that the received medicines remain safe, free from physical and chemical damage, and maintain their quality. Medication damage not only negatively impacts patients but also affects the efficiency of healthcare facilities. Healthcare facilities serve as venues for implementing various health efforts, including promotive, preventive, curative, and rehabilitative measures, conducted by the government, local authorities, or the community. As primary healthcare facilities, Puskesmas prioritize promotive and preventive efforts to improve the health status of the communities in their service areas. This study aims to analyze the compliance levels of medicine storage, arrangement in storage rooms, and warehouse requirements at Puskesmas Siring Betik and Puskesmas Wonosobo, Wonosobo District, Tanggamus Regency, in 2024. The research employed a descriptive quantitative design with a saturated sampling technique, using observation sheets guided by the standards outlined in Permenkes RI No. 74 of 2016 regarding Pharmaceutical Service Standards at Puskesmas and the 2010 Directorate General of Pharmaceutical and Medical Devices Training Materials on Pharmaceutical Management. The results showed that medicine storage compliance at both Puskesmas Siring Betik and Wonosobo reached 100%. In terms of medicine arrangement, Puskesmas Siring Betik achieved a compliance rate of 87%, while Puskesmas Wonosobo reached 100%. Regarding warehouse requirements, the compliance level at both Puskesmas was 85%. Overall, the compliance levels were 81.25% for Puskesmas Siring Betik and 84% for Puskesmas Wonosobo..